Evaluasi pencapaian break even point sebagai strategi menentukan volume penjualan optimal dengan pendekatan dynamic capability - Efendi Choiri; Dian Fahriani; Achmad Wicaksono; Chairil Anwar (Jurnal STEI Ekonomi, 2025)
Public Fuel Filling Stations (SPBU) operate within a highly dynamic and competitive business environment. Fluctuating fuel prices, Government regulations, and changing consumer behavior pose significant challenges to maintaining operational sustainability and profitability. This study examines the application of Break Even Point (BEP) analysis and the Dynamic Capability approach in determining the optimal sales volume at SPBU Siwalan Panji. The research employs a qualitative descriptive method, utilizing data collection techniques such as interviews and documentation and data analysis involving reduction, presentation, and conclusion drawing. The findings indicate that BEP analysis is critical in identifying the minimum sales volume required to avoid losses and is a strategic tool for managerial evaluation and decision-making. Moreover, implementing Dynamic Capability through the digitalization of payment systems, inventory management using IoT, and service quality improvements has proven effective in enhancing operational efficiency and customer satisfaction. These innovations enable the SPBU to adapt to environmental changes and maintain optimal sales performance. The study recommends that other SPBUs adopt an integrated application of BEP and Dynamic Capability to support sustainable business growth in the evolving fuel retail industry.